Functional and Neurophysiological Correlation of Indriya with Sensory Systems: An Integrative Review. - Dr Shubham S Zodpe; Dr Vinod M Choudhari; Dr Nikita M Sonone (Ayurline: International Journal of Research in Indian Medicine, 2026)
Background: The concept of Indriya in Ayurveda represents a comprehensive framework encompassing sensory and motor faculties responsible for perception and interaction with the external environment. Classical Ayurvedic texts describe ten Indriyas, including five Gyanendriyas (sensory faculties) and five Karmendriyas (motor faculties), each associated with specific objects of perception and action. In contrast, modern biomedical science explains sensory perception through specialized receptors, neural pathways, and cortical processing mechanisms. Aim: To analyze and establish a functional and neurophysiological correlation between the Ayurvedic concept of Indriya and the modern understanding of sensory systems. Materials & Methods: A narrative review was conducted using classical Ayurvedic texts and contemporary scientific literature. Ayurvedic references included Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya, while modern concepts were derived from standard physiology textbooks and research articles. A qualitative analysis was performed to identify similarities and differences in structure, function, and integration. Results: The Gyanendriyas were found to correlate with sensory receptor systems and afferent neural pathways, whereas the Karmendriyas correspond to motor systems involving efferent pathways and cortical control. The analysis indicates that Indriya represent integrated functional units encompassing receptors, neural transmission, and central processing rather than mere anatomical structures. Conclusion: Indriya can be interpreted as integrated neuro-functional systems when correlated with modern neurophysiology. This integrative approach bridges traditional Ayurvedic concepts with contemporary neuroscience, offering a broader understanding of sensory and motor physiology and providing potential insights for interdisciplinary research and holistic management of sensory disorders. Keywords: Gyanendriya, Karmendriya, Sensory system, Neurophysiology, Sensory perception